Erosão bruta e produção de sedimentos em bacia hidrográfica sob plantio direto no planalto do Rio Grande do Sul - Didoné, Elizeu Jonas (2013)
The impact of agriculture on water resources has been a focus for problems associated with reservoir siltation, depletion of water quality, reduced infiltration and soil water storage, formation of floods and low water availability during drought periods. In this sense the estimation of gross erosion and sediment yield monitoring reflect the dynamic that occurs in catchments and the processes observed in the rivers. Studies of erosion in grain crop agricultural areas using no-tillage systems are scarce at catchment scale. Thus, this study estimated gross erosion and sediment yield in a large catchment representative of grain crop cultivation and its potential impacts on land degradation and consequent impacts on water resources. The catchment is located on the Riograndense plateau characterized by deep and weathered soils and landscape is gently sloping. Gross erosion estimation was performed with the RUSLE model along with a Geographic Information System where the attributes of soil, climate, landscape, and land use and management were spatialized for the entire drainage area of the catchment (800 km2). The catchment is drained by the Conceição River, which includes towns such as Cruz Alta and Ijuí, among others. The hydrossedimentometric monitoring was carried out for twenty months with automatic instruments, daily sample collection and sampling during rainfall-runoff events. The variables monitored were rainfall, flow, turbidity and suspended sediment concentration. From this data set sediment yield was estimated for the period and a sediment discharge rating curve was established to extrapolate sediment yield for the last decade. The average results of gross erosion for the catchment are in the order of 8 t ha-1 year-1 and average sediment yield was 140 mg km-2 year-1, generating sediment delivery ratio values of 17.5 %. From the temporal and spatial variability of the results, this study seeks to highlight the erosion processes operating at this scale and the implications for management and water and soil conservation programs for similar regions.